2019
DOI: 10.1038/s41388-019-1069-y
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of gap junctions attenuates acute myeloid leukemia chemoresistance induced by bone marrow mesenchymal stromal cells

Abstract: The bone marrow (BM) niche impacts the progression of acute myeloid leukemia (AML) by favoring the chemoresistance of AML cells. Intimate interactions between leukemic cells and BM mesenchymal stromal cells (BM-MSCs) play key roles in this process. Direct intercellular communications between hematopoietic cells and BM-MSCs involve connexins, components of gap junctions. We postulated that blocking gap junction assembly could modify cell-cell interactions in the leukemic niche and consequently the chemoresistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…This modification in the redox status of MSCs may impact their functionality, since a defective support of normal hematopoiesis by MSCs stimulated by leukemic cells has been reported [ 57 ]. Our group recently highlighted a specific profile of connexins, which are components of gap junctions, in leukemic MSCs [ 58 ]. The reversed ROS kinetics, namely drop in leukemic cells and rise in MSCs, may be partly explained by a previously described mechanism of ROS transfer between hematopoietic cells and MSCs by Connexin-43 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This modification in the redox status of MSCs may impact their functionality, since a defective support of normal hematopoiesis by MSCs stimulated by leukemic cells has been reported [ 57 ]. Our group recently highlighted a specific profile of connexins, which are components of gap junctions, in leukemic MSCs [ 58 ]. The reversed ROS kinetics, namely drop in leukemic cells and rise in MSCs, may be partly explained by a previously described mechanism of ROS transfer between hematopoietic cells and MSCs by Connexin-43 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting gap junctions, CBX has been reported to synergize the effects of cytarabine to overcome chemoresistance. This indicates that it is possible to develop therapies to overcome the formation of chemoresistance and to eradicate leukemic cells [ 63 ].…”
Section: Leukemic Bone Marrow Nichementioning
confidence: 99%
“…These results suggested that AML cells might establish gap junction interactions to transfer ROS to MS-5 cells when in co-culture. To test this hypothesis, we used the calcein-AM dye, which can only be transferred via gap junctions [10]. We labelled stromal cells with calcein-AM, cultured them with unlabelled AML cells and analysed the fluorescence of AML cells after three hours.…”
Section: Resultsmentioning
confidence: 99%
“…Functional gap junction presence was evaluated using the fluorescent dye Calcein-AM green (Invitrogen, C1430) adapting a previously established protocol [10]. MS-5 cells were stained with 500 nM Calcein-AM dye in complete cell culture medium for 1 hour at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation